Winning at innovation the A-to-F model - Trias de Bes, Fernando; Kotler, Philip (Palgrave Macmillan, 2011)
Innovation is a responsibility normally assigned to R&D departments but this is not enough. Companies need a systematic framework so innovation can occur at different levels of the organization. The world's leading expert in marketing and innovation Philip Kotler, and Fernando Trias de Bes together present a revolutionary model for innovation